MOTIF DAN KEPUASAN GENERASI MILENIAL KOTA DENPASAR MENDENGARKAN PODCAST MELALUI SPOTIFY - Sugiantari, Ni Kadek Dilla; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
ABSTRACT Podcasts are on-demand audio files uploaded on the platform to be heard anytime and anywhere. Podcasts can currently be heard through the Spotify music streaming app with a wide variety of genres. The use of media by individuals is influenced by motives. This study aimed to find out what the motives and how the satisfaction of millennials in Denpasar in listening to podcasts through Spotify. The media consumption motives used in this study is Uses and Gratifications Theory forward by Papacharissi and Rubin. This study uses descriptive quantitative method with purposive sampling. Data were obtained by distributing questionnaires using Likert scale. The data analysis techniques used are descriptive statistics comparing the average score of motives and satisfaction. The results showed that there five motives that can be satisfied in listening podcast trough Spotify are information motive, utility motive, convenience motive, pass time motive, and entertainment motive. Keyword: Podcast, Motive, Satisfaction, Denpasar